How firm organizations adapt to secure a sustained knowledge transfer - Ulrich Witt; Christian Zellner (Max Planck Institute of Economics, 2007)
New knowledge with potential commercial value is created, replicated, and transferred in a distributed manner. The highly systemic nature of knowledge production and the need for any knowledge to be individually acquired and expressed in order to produce an effect, jointly constrain the dynamics of knowledge commercialization. This paper analyzes the nature of these constraints from an individualistic perspective, focusing particularly on the often neglected entrepreneurial aspects of the knowledge transfer. It explains how the constraints are overcome by organizational adaptations inside firms so that a sustained knowledge transfer into the commercial sphere of the innovation system can be secured.
Keywords: D23; D83; J24; M13; M51; O31; O40; 330; Wissenstransfer; Unternehmer; Organisatorischer Wandel; Wissensmanagement